Stereoelectronic effects in the reaction of aromatic substrates catalysed by Halomonas elongata transaminase and its mutants - Contente, Martina Letizia; Planchestainer, Matteo; Molinari, Francesco; Paradisi, Francesca (Royal Society of Chemistry, 2016)
A transaminase from Halomonas elongata and four mutants generated by an in silico-based design, were recombinantly produced in E. coli, purified and applied to the amination of mono-substituted aromatic carbonyl-derivatives. While benzaldehyde derivatives resulted excellent substrates, only NO2-acetophenones were transformed into the (S)-amine with high enantioselectivity. The different behaviour of wild-type and mutated transaminases was assessed by in silico substrate binding mode studies.